Unidirectional ripples in strained graphene nanoribbons with clamped edges at zero and finite temperatures - Baimova, Julia A. (2013)
Molecular dynamics simulations based on many-body interatomic potentials are conducted to investigate the formation of unidirectional ripples in zigzag and armchair graphene nanoribbons with clamped edges under in-plane uniform strain. The ripple formation is found to be a result of buckling under in-plane membrane forces having compressive and tensile principle components. This study demonstrates that the amplitude and orientation of the unidirectional ripples can be controlled by a change in the components of the applied strain. The ripple wavelength is practically independent of the applied strain but increases with the increasing nanoribbon width. In the study of the temperature effect on strain-induced ripples it was found that with increase in temperature the degree of fluctuation of ripples increases. Ripples with larger formation energy are less affected by thermal fluctuations.